Openness, Human Development, and Fiscal Policies : Effectson Economic Growth and Speed of Adjustment - Villanueva, Delano (IMF Working Papers; Working Paper ;, 1993)
The model developed here postulates that learning through experience plays a critical role in raising labor productivity over time, with three major consequences. First, the steady-state growth rate (of output) becomes endogenous and is influenced by government policies. Second, the speed of adjustment to steady-state growth is faster, and enhanced learning further reduces adjustment time. Third, both steady-state growth and the optimal net rate of return to capital are higher than the sum of exogenous rates of technical change and population growth. Simulation results confirm the model's faster speed of adjustment, while regression analysis explains a large part of divergent growth patterns across countries in terms of the extent of openness and human development and of the quality of fiscal policies.